Clio contra el Imperio, Historiografía anglosajona sobre Hispanoamérica en los siglos XVIII - XIX - Quiroz Chueca, Francisco (2005)
This article analyzes the role played by Anglosaxon historiography in the conflict between England and US of eighteenth and nineteenth centuries, and the decadent Spain. English and later American historians used historical pictures to illustrate the decadence of the Hispanic and Catholic world and, at the same time, justify the necessity of Hispanic America to re-orient itself towards the Anglosaxon and Protestant world.